Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Quality Control Points - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS)
AN173 includes pages 43-91 of the Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. It describes management approaches for five areas of quality concern: breeding and genetic selection, utilization of animal health products and practices, processing/cattle handling, nutrition, and culling management. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006.